2000
DOI: 10.1159/000023539
|View full text |Cite
|
Sign up to set email alerts
|

New Medical Approaches in Pituitary Adenomas

Abstract: Recently, the medical approach to patients with secreting and clinically non-functioning pituitary adenomas has received great impulse thanks to the availability of new, selective and long-lasting compounds with dopaminergic activity, such as cabergoline, and of somatostatin analogues provided in slow-release formulations, such as lanreotide and octreotide long acting release (LAR). In particular, the use of cabergoline has induced control of hyperprolactinaemia and tumour shrinkage in the great majority of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
13

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 78 publications
(162 reference statements)
1
33
0
13
Order By: Relevance
“…These data would indicate a stimulatory role for SSTR5 in NFA cell proliferation, suggesting that the use of compounds selectively interacting with SSTR5 in NFA medical therapy might be counterproductive. In addition, this effect might account for the lack of volume reduction (Colao et al 2000, Andersen et al 2001 or the increase in tumor volume (Gasperi et al 1993) observed in NFA patients treated with octreotide or lanreotide, which mainly interacts with SSTR2 and SSTR5. However, this does not seem to be a general mechanism in pituitary adenomas, because previous evidence from somatotroph and corticotroph pituitary tumors suggests that the additional activation of SSTR5 might be responsible for the enhanced efficacy of SRIF analogs in reducing both secretion and cell proliferation (Shimon et al 1997, Hofland et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…These data would indicate a stimulatory role for SSTR5 in NFA cell proliferation, suggesting that the use of compounds selectively interacting with SSTR5 in NFA medical therapy might be counterproductive. In addition, this effect might account for the lack of volume reduction (Colao et al 2000, Andersen et al 2001 or the increase in tumor volume (Gasperi et al 1993) observed in NFA patients treated with octreotide or lanreotide, which mainly interacts with SSTR2 and SSTR5. However, this does not seem to be a general mechanism in pituitary adenomas, because previous evidence from somatotroph and corticotroph pituitary tumors suggests that the additional activation of SSTR5 might be responsible for the enhanced efficacy of SRIF analogs in reducing both secretion and cell proliferation (Shimon et al 1997, Hofland et al 2005.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, our data show that the SSTR2 selective agonist did not influence NFA cell viability, which was promoted by the SSTR5 selective agonist. This effect might explain the lack of efficacy of medical treatment by means of octreotide or Lan, compounds mainly interacting with SSTR2 and less with SSTR5, in some NFA (Oppizzi et al 1998, Andersen et al 2001, Colao et al 2000, Gasperi et al 1993. Moreover, our findings might provide a possible …”
mentioning
confidence: 99%
“…Side effects from this drug include GI distress and gynecomastia, occurring in fewer than 15% of patients. 19,50 Elevated levels of hepatic transaminases are also common, thus requiring periodic monitoring of liver function tests. Because of its favorable adverse effect profile, twice-daily dosing, and relative effectiveness as a single-agent therapy, ketoconazole has emerged as the agent of choice for the medical treatment of Cushing disease.…”
Section: Inhibition Of Steroidogenesismentioning
confidence: 99%